Composition of amino acids and bioactive amines in common wines of Brazil (Acta Scientiarum. Health Sciences, 2014)
Since most consumed wines in Brazil are common wines and since their representativeness is not accounted for in scientific research, current study quantifies bioactive amines and their precursors in Brazilian sweet and dry common wines, correlates the formation of amines with physical and chemical parameters and clusters studied areas by their amine and amino acid contents. Forty-seven wine samples varying in type, color and origin were analyzed simultaneously for seventeen amino acids, ammonium ion and five bioactive amines by reversed-phase high performance liquid chromatography and ultraviolet detection after the derivation phase. Physical and chemical analyses comprised titratable acidity, pH, organic acids, sugar and alcohol contents. Sweet wines had lower concentrations of amino acids and bioactive amines. Dry white wines had higher amino acid contents when compared to those in dry red wines. Since multivariate data analysis confirmed similarities between the studied regions, their unity as potential viniculture area was reinforced. Amine levels in Brazilian common wines were reported for the first time and results reinforced the importance of bioactive amines quantification and the use of suitable vinification practices to reduce their formation.